STRATEGI INDONESIA MENJAGA KEAMANAN WILAYAH PERBATASAN TERKAIT KONFLIK LAUT CINA SELATAN PADA TAHUN 2009-2014 - Akmal "; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes how the Indonesian strategy to maintain security-related border areas of the South China Sea conflict in 2009-2014. South China Sea conflict until now have been not found a point of completion. Conflict continues to grow with the increasing military power among claimant states. Escalation of the conflict surely threaten security in the region. Although not a claimant states, Indonesia have a direct border with the South China Sea and has an interest in those waters, that is political, economic and security stability. Indonesia conducted a series of steps to secure its interests in the form of a decision as Indonesia in maintaining security strategy, especially directly adjacent to the South China Sea. This research used qualitative methods, and approaches realism. Using the analysis of the nation-state level and using the theory of security strategy. Results of this research is the increasing capability of Indonesian military capability enhancement through minimum essential force (MEF) 2010-2014. The addition of the number of troops and military fleets in Natuna as a form of Indonesia's readiness to face any possibility of conflict. Then preventive diplomacy by Indonesia went well for reducing conflict among the claimant states. To increased border management by negotiating border lines with neighboring countries and increase activity in the border region in the form of oil exploration in the waters of Natuna as a form of existence Indonesia in that area.keyword : conflict, diplomacy, security, south china sea